The Use of Germination Indices for Salinity Tolerance Classification of Pepper Cultivars - Gamze Kaya (Turkish Journal of Agriculture: Food Science and Technology)
The study aimed to evaluate the use of germination indices as a screening tool for salinity tolerance during germination and early seedling growth of pepper cultivars, and to distinguish the potential for genetic responses to salt tolerance. In the study, the seeds of seven pepper cultivars were germinated at increasing NaCl levels of 5, 10, 15 and 20 dS/m and distilled water as the control treatment for 14 days. Germination percentage (GP), mean germination time (MGT), germination index (GI), germination stress tolerance index (GSTI), seedling length (SL), seedling fresh weight (SFW) and vigor index (VI) were investigated. Results showed that germination percentage decreased with increasing NaCl levels while the highest germination percentage at 20 dS/m was 92% in BT Burdem with no significant reduction. Seedling growth of pepper cultivars was severely inhibited by increasing salinity stress. SFW was depressed depending on reduction in SL due to increasing NaCl. BT-Burli and BT İnce Sivri were the most tolerant cultivars to NaCl and they were used for genetic resources towards salinity. Seedling growth was much more sensitive to salinity than germination because of the highest percent reduction in seedling growth parameters. Among the parameters, GSTI gave the highest significant correlation coefficient with SL and SFW; indicating that it would be useful for estimating seedling growth. It was concluded that genotypic variation was observed among pepper cultivars for salinity tolerance and GSTI could be used for a predictor for salinity tolerance.